Atorvastatin Inhibits Inflammatory Response, Attenuates Lipid Deposition, and Improves the Stability of Vulnerable Atherosclerotic Plaques by Modulating Autophagy - Peng, Shi; Xu, Long-Wei; Che, Xin-Yu; Xiao, Qing-Qing; Pu, Jun; Shao, Qin; He, Ben (Frontiers in Pharmacology, 2018)
Atherosclerosis is a chronic disease comprising intima malfunction and arterial inflammation. Recent studies have demonstrated that autophagy could inhibit inflammatory response in atherosclerosis and exert subsequent atheroprotective effects. Our previous study also demonstrated the role of autophagy in the inhibition of inflammation by atorvastatin in vitro. Therefore, in the present study, we aimed to determine whether atorvastatin could upregulate autophagy to inhibit inflammatory cytokines secretion, lipid accumulation, and improve vulnerable plaque stability, both in vitro and in vivo. First, we established a vulnerable atherosclerotic plaque mouse model through partial ligation of left common carotid artery and left renal artery to explore the effect of atorvastatin on vulnerable plaques. The results showed that atorvastatin could enhance the stability of vulnerable atherosclerotic plaques and reduce the lesion area in the aorta. Atorvastatin could also inhibit NLRP3 inflammasome activation and inflammatory cytokines, such as IL-1β, TNF-α and IL-18 secretion in vivo. Atorvastatin treatment upregulated the expression of autophagy-related protein microtubule-associated protein light chain (LC3B) and downregulated the expression of SQSTM1/p62, which suggested that autophagy was activated in vulnerable plaques. Transmission electron microscopy further demonstrated the atorvastatin-induced increase in autophagy activity in vulnerable atherosclerotic plaques. We employed oxidized low-density lipoprotein (ox-LDL) to stimulate RAW264.7 cells with atorvastatin, which showed that atorvastatin could attenuate lipid deposition, ameliorate inflammation, inhibit NLRP3 inflammasome activation, and enhance autophagy in vitro. All these beneficial effects were abolished by 3-methyladenine treatment, an autophagy inhibitor. Atorvastatin also significantly inhibited the phosphorylation of mTOR, which strongly suggested the involvement of the mTOR pathway. Our study proposed a new role for atorvastatin as an autophagy inducer to exert anti-inflammatory and atheroprotective effects, to stabilize vulnerable atherosclerotic plaques.